Association of Social Jetlag With Sleep Quality and Autonomic Cardiac Control During Sleep in Young Healthy Men - Sűdy, Ágnes Réka; Ella, Krisztina; Bódizs, Róbert; Káldi, Krisztina (Frontiers in Neuroscience, 2019)
Social jetlag (SJL), the difference in sleep timing between work and free days is a consequence of the discrepancy between the individual’s circadian rhythm and the social clock. SJL is considered a chronic stress factor and has been linked to various health problems. In this field study, we examined for the first time the association between SJL and cardiac regulation during sleep. 33 healthy young men aged 20–26 years participated in the study. The median SJL was used as a cut-off value to assign the participants into two groups with either lower or higher SJL. As a marker of autonomic control we analyzed heart rate variability (HRV) and addressed intra-individual differences between workdays and free days. In subjects with higher SJL, pNN50, an indicator of vagal activity was lower in the first 3 h of sleep on workday as compared to free day (day × sleep block × group, p = 0.015), indicating a more adaptable regulation on free days, when subjects slept according to their own preference. However, in subjects with lower SJL, no HRV differences were found between the two nights. SJL showed correlation with the free day-workday differences of both pNN50 and another vagal index, RMSSD in the first 2 h of sleep (p = 0.023 and 0.047, respectively). In subjects with higher SJL, a different HF power on workdays and free days (p = 0.031) also indicated that a shift in sleep timing is accompanied by an altered parasympathetic activity in the first few hours of sleep. Furthermore, subjective sleep quality on workdays was negatively associated with SJL (p = 0.02), and subjects with higher SJL reported worse sleep quality on workday than on free day (p = 0.027). Taken together, our data call attention on the potential effect of SJL on sleep quality and vagal activity during sleep.